PENGGUNAAN ALAT PERAGA METERAN UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA BAGI SISWA BERKESULITAN BELAJAR MATEMATIKA - Mujahid, Fauzi Nahwah (Pendidikan Luar Biasa, 2013)
Latifa. THE USE OF METER PROPS TO IMPROVE THE MATHEMATICS LEARNING ACHIEVEMENT OF MULITIPLICATION SUBJECT IN MATHEMATICS LEARNING DISABILITY III GRADERSOF SDN KARTODIPURAN SURAKARTA IN THE SCHOOL YEAR OF 2012/2013. Skripsi, Surakarta: Teacher Training and Education Faculty of Sebelas Maret University. April. 2013. The objective of this research is to find out the us of  meter props to improve the mathematics learning achievement of multiplication subject in mathematics learning disability III graders of SDN Kartdoipuran Surakarta in thee school year of 2012/2013. This research employed with classroom action research method. The subjects of this research were 2 students with learning disability consisting of a boy and a girl. The metthods of data collection were observation technique, test and document analysis. The technique of analyzing data were descriptive comparative and critical analysis. Considering the result of research it can be concluded that the used of meter props can improve the mathematics learning achievement of multiplication subject in learning disability III graders of SDN Kartodipuran Surakarta in the school year of 2012/2013. Key words: meter props, mathematics learning achievement, learning disability.